PENGARUH MODEL PROJECT BASED LEARNING PEMBELAJARAN MATEMATIKA MATERI PECAHAN TERHADAP HASIL BELAJAR SISWA KELAS IV SD - Nurafni Mangunsong; Putri Juwita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the effect of the Project Based Learning model on the mathematics learning outcomes of fourth-grade elementary school students. This is an experimental study using a one-group pre-test and post-test design. The method used is experimental with a quantitative approach. The study involved all students with a total learning outcome score of 1293.75. In the pre-test phase, the highest score obtained by students was 51, with an average score of 30. After the implementation of the Project Based Learning model, the maximum post-test score increased to 68. The analysis results showed that the significance value in the pre- test was 0.05, indicating no significant difference at the initial stage. However, the post-test result showed a significance value of 0.749, which is also greater than 0.05. This study illustrates that a project-based approach can be an alternative for improving the quality of learning in elementary schools.